2018
DOI: 10.1177/0149206318799443
|View full text |Cite
|
Sign up to set email alerts
|

What Are We Explaining? A Review and Agenda on Initiating, Engaging, Performing, and Contextualizing Entrepreneurship

Abstract: Entrepreneurship is multifaceted. The purpose of this review is to acknowledge and critically assess the many and varied dependent variables (DVs) of entrepreneurship over the last 17 years. By focusing exclusively on systematically reviewing entrepreneurship’s DVs, this paper maps out, classifies, and provides order to the phenomena that scholars consider part of this self-defined field of research. Using a systematic selection process and an inductive approach to categorization, we offer a meta-framework for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
186
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(197 citation statements)
references
References 376 publications
(388 reference statements)
6
186
0
5
Order By: Relevance
“…In their retrospective on SEJ , Wright and Hitt () found that only 0.6% of articles addressed the theme in the Journal's first 5 years and only 2.6% did so in the subsequent 5‐year period. Likewise, in their survey of the main dependent variables in entrepreneurship research, Shepherd, Wennberg, Suddaby, and Wiklund () found that the field was focused on “the (a) initiation, (b) engagement, and (c) performance of entrepreneurial endeavors embedded in (d) environmental conditions,” confirming the relative neglect of research and theory on change as an outcome of entrepreneurial actions.…”
Section: History and Entrepreneurship Theory: Connecting Time Contexmentioning
confidence: 97%
See 1 more Smart Citation
“…In their retrospective on SEJ , Wright and Hitt () found that only 0.6% of articles addressed the theme in the Journal's first 5 years and only 2.6% did so in the subsequent 5‐year period. Likewise, in their survey of the main dependent variables in entrepreneurship research, Shepherd, Wennberg, Suddaby, and Wiklund () found that the field was focused on “the (a) initiation, (b) engagement, and (c) performance of entrepreneurial endeavors embedded in (d) environmental conditions,” confirming the relative neglect of research and theory on change as an outcome of entrepreneurial actions.…”
Section: History and Entrepreneurship Theory: Connecting Time Contexmentioning
confidence: 97%
“…In their retrospective on SEJ, Wright and Hitt (2017) found that only 0.6% of articles addressed the theme in the Journal's first 5 years and only 2.6% did so in the subsequent 5-year period. Likewise, in their survey of the main dependent variables in entrepreneurship research, Shepherd, Wennberg, Suddaby, and Wiklund (2019) found that the field was focused on "the (…”
Section: History and Entrepreneurship Theory: Connecting Time Contmentioning
confidence: 99%
“…These factors are called by North (1990) as institutions, which can enable or constrain entrepreneurship, including the start-up rate and firm growth. The enterprises do not have the power to control or manipulate these institutions (Shepherd et al, 2019;Draskovic et al, 2019). Scholars link entrepreneurship (Stenholm et al, 2013) with institutions (Baumol, 1990;North, 1990;Sobel, 2008) by arguing that institutional environment, consisting on regulatory framework, legislation and social norms, creates the proper circumstances for adults to make decisions, which is vital in entrepreneurial cognition (Zajkowski & Domańska, 2019;Pinho, 2017;Raza et al, 2018;Sobel, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have demonstrated that different factors originated from within and outside organizations influence their entrepreneurial activity (Shepherd et al, 2019;Rogalska, 2018). Institutional environment is seen as a critical component in understanding the level of entrepreneurial activity (Bjørnskov & Foss, 2016;Bowen & De Clercq, 2008;Chowdhury et al, 2015;Grilli et al,2018;Stenholm et al, 2013;Yay et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Shepherd et al . (2019) even created a theoretical framework that reviewed entrepreneurship from four factors, namely, initiating, engaging, performing, and contextualizing. The second approach reviews entrepreneurship study by focusing on scholars and citations.…”
Section: Introductionmentioning
confidence: 99%